When Tiny was tiny - Meister, Cari.; Davis, Rich, 1958- (New York : Viking, 1999)
A dog's owner describes how Tiny grew from a very small puppy to a very big dog.
"Ages 4-7"--cover p. [4].
3 4 9 10 13 19 31 33 34
Keywords: Dogs -- Fiction; Size -- Fiction